An applicability of hypercontos in the portuguese classes (Research, Society and Development, 2019)
This article aims to reflect on the applicability of hypercontos in Portuguese language classes, because it understands that this textual genre contributes significantly to the formation of proficient readers, in addition to bringing students closer to the reading universe. This is justified by the fact that the target audience of the current schools is composed mostly of "immersive" readers (Santaella, 2004), that is, the students are Internet users who navigate frequently in cyberspace networks, composed of links, images, videos, audios, among other languages. This reader profile finds in the hypertales the interaction that is accustomed, since these hypertexts take advantage of the potentialities of the virtual environment to materialize. In this way, this research of qualitative approach used the contributions of scholars such as Hayles (2009), Dias (2012) Santaella (2004) and Cosson (2011), with the intention of constructing and applying a didactic sequence of the hyperconto “Uma Barulho no Porão” basement "by Marcos Cecílio (2014). The experience had as target audience a 2nd grade high school class from a public school in the municipality of Choró / CE. The results obtained evidenced the interest of the students in the didactic sequence in question, mainly because an interactive hypertext was used, marked by the presence of links and a non-linear narrative, which makes possible the construction of reading paths. Therefore, the use of literary hypertexts is one of the possible ways to arouse students' interest in reading, since this textual genre uses interactive and dynamic resources that attract these young internauts.